Correlation between Clean and Healthy Behavior and ARI Incidence in the Work Area of the Morosi Community Health Center, Konawe Regency - Tawakkal; Ira Nurmala; Lisnawati; Fajar Kurniawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Morosi Community Health Center in 2020 with a total of 6392 visits seen from data on the 10 biggest diseases, namely ISPA 672, Hypertension 360 visits, joints and connective tissue 132 people, nerves 2 (two) visits, stomach ulcers 384 visits, Diabetes Mellitus 48 people, Dyspepsia 156 people, Diarrhea 216 people, eye disease 30 people and other diseases 4,392 people. The aim of the study was to analyze the relationship of PHBS factors with the incidence of ARI in Morosi District, Konawe Regency. This research method is quantitative, the research results are known. It is known from the results of the Chi-Square test that the value of 56,071 is greater than X2, so it can be concluded that there is a significant relationship between PHBS and ISPA events and the Phi value is 0.438 which means it has a moderate relationship. The conclusion is that there is a moderate relationship between PHBS and ISPA